Reflecting on the Plight of Magars in Modern Nepal (Shodhmala शोधमाला, 2026)
The article charts how the Magars from being important Gorkha monarchs’ supporters in the Middle Ages and helping to unite the country were sidelined from governance and ultimately have ended up in unjust imprisonment, forced identity changes, and state violences like the Romeo and Kilo Sierra Two police operations during the 10-year Maoist insurgency. With 29 Heads of State in 35 years (from 1990 to 2025), the recent Gen Z upheaval of September 8/9 2025 is a stark demonstration of Loktantrik democratic governments of Nepal’s miserable failure in the last three decades. This failure is not only for the Magars but also for the over three and half million young Nepalese who, due to non-creation of job opportunities in Nepal, are forced to go abroad just to keep their family’s kitchen fires burning back home!